Profiles of family participation in Compulsory Secondary Education - Hernández-Prados, María-Ángeles; García-Sanz, Maria-Paz; Parra-Martínez, Joaquín; Gomariz Vicente, María-Ángeles (Anales de Psicología / Annals of Psychology, 2018)
The participation of families in the education of children who attend Compulsory Secondary Education (ESO) through the application of a questionnaire is analyzed. The initial sample consisted of 5022 families residing in 16 autonomous communities of Spain, although the actual sample consisted of 3982 parents whose children attended ESO in 96 schools. After identifying the characteristics of these fathers and mothers, considering a series of sociodemographic variables and family participation, the parental participation profiles are described through a two-stage cluster analysis that makes up three different models of family participation: Spanish families with moderate participation and low sentiment of belonging; families of non-Spanish origin with low participation and moderate feeling of belonging; and finally, Spanish families with high participation and a high feeling of belonging. The interest of the research lies fundamentally in two realities: firstly, the choice of ESO, since it is the stage least treated in studies of family participation within compulsory schooling in Spain. And secondly because it breaks with the existence of a single bipolar bifurcation that is reduced to the existence or not of participation. There are multiple variables that affect the ways of participating in the educational process of the children and that involve the configuration of the profiles obtained in this study.